DOI: 10.1007/978-3-540-87479-9_47
|View full text |Cite
|
Sign up to set email alerts
|

Tight Optimistic Estimates for Fast Subgroup Discovery

Abstract: Abstract. Subgroup discovery is the task of finding subgroups of a population which exhibit both distributional unusualness and high generality. Due to the non monotonicity of the corresponding evaluation functions, standard pruning techniques cannot be used for subgroup discovery, requiring the use of optimistic estimate techniques instead. So far, however, optimistic estimate pruning has only been considered for the extremely simple case of a binary target attribute and up to now no attempt was made to move … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 17 publications
0
84
0
Order By: Relevance
“…An essential technique for efficient discovery showed to be pruning based on optimistic estimates [22,25]. As Grosskreutz et al showed, the efficiency of the pruning is strongly influenced by the tightness of the bounds [15]. A more general method to derive optimistic estimates for a whole class of interestingness measures, that is, convex measures, was introduced in [20] and later extended in [26].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…An essential technique for efficient discovery showed to be pruning based on optimistic estimates [22,25]. As Grosskreutz et al showed, the efficiency of the pruning is strongly influenced by the tightness of the bounds [15]. A more general method to derive optimistic estimates for a whole class of interestingness measures, that is, convex measures, was introduced in [20] and later extended in [26].…”
Section: Related Workmentioning
confidence: 99%
“…A key technique to improve runtime performance of subgroup discovery in general is the application of optimistic estimates, that is, upper bounds for the interestingness of any specialization of the currently evaluated pattern. Although research has shown that improving the tightness of the utilized bounds improves the runtime performance substantially [15], there has been no extensive research so far concerning upper bounds for generalization aware interestingness measures beyond the trivial transfer of bounds for traditional measures.…”
Section: Introductionmentioning
confidence: 99%
“…All numerical attributes where discretized using minimal entropy discretization. As representative traditional subgroup miner we used the state-of-the-art algorithm Dpsubgroup [10]. All involved algorithms were implemented in Java and will be published on the author's webpage.…”
Section: Empirical Evaluationmentioning
confidence: 99%
“…Hence they create an anti-monotone search space that contains the family of all interesting descriptions. While our algorithms use equivalence classes instead of individual descriptions, all the optimistic estimator techniques including recent findings [10] can still be applied. Consequently, our algorithms always use a condensed version of traditional method's search spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain efficiency, these algorithms typically rely on top-down search combined with considerable pruning, exploiting either anti-monotonicity of the quality measure (e.g. frequency), or so-called optimistic estimates of the maximally attainable quality at every point in the search space (Grosskreutz et al 2008). With small datasets and simple tasks, these tricks work well and give complete solutions in reasonable time.…”
Section: Introductionmentioning
confidence: 99%